Transforming the 2019-2020 Protest Agenda on Social Network Sites - Belyakov, Alexey; Sokolov, Alexander; Mironova, Svetlana; Frolov, Alexander; Isaeva, Elena (Journal of Sociology: Bulletin of Yerevan University, 2021)
Social network sites have taken a strong position in the space of socio-political communication. In the modern world, the necessity to analyze events occurring in the virtual space for a relevant reaction to events occurring in reality, is generally recognized. The study of online processes is largely based on the analysis of quantitative data that allows talking about the activity of users and their involvement. However, the meaning of the information transmitted in social networks remains important. In the framework of this study, an attempt is made to determine the specifics of broadcasting protest agendas in social networks and the impact of their transformation on the process of involving users in online protest activity. Examples of 7 protest campaigns accompanied by active coverage in social networks are given. Conclusions are drawn about the specifics of broadcasting protest agendas in social networks and supporting users from their transformation.